1973
DOI: 10.1530/jrf.0.0320491
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Count, Morphology and Motility After Unilateral Mumps Orchitis

Abstract: In earlier studies carried out between 1951 and 1970, a total of 298 patients with mumps orchitis were examined in the Sexological Institute in Prague (Bart\l=a'\k, Nedoma & Mirovsk\l=y'\,1955; Sk\l=a' \lov\l=a' \,Bart\l=a'\k & Neva\l=r%v\ilov\l=a' \,1966; Bart\l=a'\k, Sk\l=a'\lov\l=a'\& Neva\l=r%v\ilov\l=a' \,1968). This number included 178 adults between 19 and 53, and 120 youths between 13 and 18 years of age. The findings can be summarized as follows. (1) Adults suffered more frequently (29%) than youths (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 1 publication
0
27
0
1
Order By: Relevance
“…Mumps is caused by an RNA virus of the paramyxovirus group. In prepubertal boys, the symptoms of mumps are usually limited to infectious parotitis, but, in men, orchitis is the most common complication (29,34). Orchitis develops in 5 to 37% of all adult patients infected with mumps (120).…”
Section: The Human Testismentioning
confidence: 99%
See 1 more Smart Citation
“…Mumps is caused by an RNA virus of the paramyxovirus group. In prepubertal boys, the symptoms of mumps are usually limited to infectious parotitis, but, in men, orchitis is the most common complication (29,34). Orchitis develops in 5 to 37% of all adult patients infected with mumps (120).…”
Section: The Human Testismentioning
confidence: 99%
“…Within the first few days of infection, the virus directly attacks the testes, destroying the testicular parenchyma (44,242) and decreasing androgen production (4). This accounts for the testicular atrophy observed in 40 to 70% of patients with orchitis (29,34). Unilateral involvement is the most common, while bilateral involvement occurs in 15 to 30% of the patients with orchitis (201).…”
Section: The Human Testismentioning
confidence: 99%
“…The resulting inflammation within the inelastic tunica albuginea causes swelling, further pressure necrosis, and cell death. Conservative treatment of mumps orchitis consisting of analgesics, bed rest, and elevation of the scrotum results in testicular atrophy in 40%-70°70 of cases and in sterility in 30% -87% of men [5,7], although a recent series of conservatively treated, mild cases of mumps orchitis reported no incidence of sterility [99]. Burhans [12] and Nixon et al [79] reported that early incision of the tunica albuginea and drainage of the hydrocele to relieve the pressure necrosis of the testicle decreased the incidence of testicular atrophy but failed to prevent sterility in 12%0-30% of patients.…”
Section: Infectionmentioning
confidence: 99%
“…This pathologic process leads to testicular atrophy. Studies performed in different periods reported testicular atrophy rates of 40 and 70% [13,22,23].…”
Section: Discussionmentioning
confidence: 99%